Smash : using market shaping to design new strategies for innovation, value creation, and growth - Nenonen, Suvi; Storbacka, Kaj (Emerald Publishing Limited, 2018)
Stunningly, strategy has never adequately defined one of its central institutions, the market. Old playbooks got away with a hodgepodge of assertions, assumptions and approximations. But the undeniable complexity of modern markets confronts us with the truth. Markets are elaborate, evolving ecosystems - think biology, not machinery. Today, strategy must embrace complexity or die. Recognizing markets as complex adaptive systems spells strategic implications. Notably, as markets are partly socially constructed, they can be reconstructed. And while they cannot be predicted or controlled, they can be influenced. Rooted in the richness of market systems, SMASH traces the three main resulting shifts in strategic thinking: (1) from firm focus to context focus, where the relevant context is our definition of the market; (2) from competing and winning to value creation and cooperation; and (3) from analysis, prediction and planning to non-predictive strategizing and experimentation. Nenonen and Storbacka weave these three strands together into a cohesive strategic framework: Strategies for Market Shaping. Market shaping strategies acknowledge that much of firm performance is explained by the markets where a firm operates. Crucially, strategic choices go beyond market selection, entry and exit; firms should actively seek to adapt the market to the firm instead of the firm to the market, and open up untapped value in the process. Market shaping is not new. What is new is systematizing an actionable framework for understanding and shaping markets. And the good news: It does not take market power and resources, or intuitive genius, to shape markets to your own benefit. SMASH offers tangible strategies that savvy market shapers of any size can implement, making it a must-read.
Includes bibliographical references and index.
Print version record
Keywords: Marketing; Business & Economics -- Marketing -- General; Business strategy